2019
DOI: 10.1177/1479973119882939
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a pulmonary rehabilitation programme in primary care in Greece: A FRESH AIR implementation study

Abstract: Pulmonary rehabilitation (PR) is an evidence-based, low-cost, non-medical treatment approach for patients with chronic respiratory diseases. This study aimed to start and assess the feasibility, acceptability and impact of a PR programme on health and quality of life of respiratory patients, for the first time in primary care in Crete, Greece and, particularly, in a low-resource rural setting. This was an implementation study with before–after outcome evaluation and qualitative interviews with patients and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…These findings may be related to disease progress, or GPs’ improved adherence to guidelines, or both. Other CME projects have led to increased use of pulmonary rehabilitation 17 , so we reason that the CME in in this study may have had similar effects. Previously published results on PRIMAIR’s baseline data showed that the participating GPs had a high level of knowledge about smoking cessation support 18 , yet they rarely offered smoking cessation support to patients 19 .…”
Section: Discussionmentioning
confidence: 82%
“…These findings may be related to disease progress, or GPs’ improved adherence to guidelines, or both. Other CME projects have led to increased use of pulmonary rehabilitation 17 , so we reason that the CME in in this study may have had similar effects. Previously published results on PRIMAIR’s baseline data showed that the participating GPs had a high level of knowledge about smoking cessation support 18 , yet they rarely offered smoking cessation support to patients 19 .…”
Section: Discussionmentioning
confidence: 82%
“…It was essential that space for the program be located on a ground floor next to a major entrance and adjacent to a washroom to accommodate potential mobility challenges of participants. Structural considerations such as free parking, access, and timing of programs have been identified as either anticipated factors or known to be an impediment to participation and retention of clients in similar programs [8][9][10]27]. To that end, we either assisted participants by parking their vehicle for them or absorbed transit costs to decrease physical and economic barriers to the program.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the hesitance of patients to participate in the Pulmonary Rehabilitation Programme, 60 we had to introduce a component in the programme that emphasised the benefits of exercise for respiratory symptoms.…”
Section: Perceived Causes/ Susceptibilitymentioning
confidence: 99%
“…We embraced this norm as a motivator in the Pulmonary Rehabilitation Programme. 60 We capitalised on the positive social pressure to exercise together as a group and help each other to complete the programme by not…”
Section: Norms/ Barriersmentioning
confidence: 99%